Are MPAs effective in removing fishing pressure from benthic species and habitats? - Langton, Rebecca; Stirling, David A.; Boulcott, Philip; Wright, Peter J. (Biological conservation, 2020)
MPAs are expected to improve the conservation status of rare and important habitats and species. However, the reduction in anthropogenic pressure due to such management measures is rarely estimated. Although MPA networks may cover a large proportion of the seabed, designated areas that prohibit damaging fishing activity are often much smaller. This case study compares fishing pressure inside and outside areas covered by Scottish MPAs and MPA management measures, further relating its distribution to bottom ruggedness, which influences benthic communities and their exposure to mobile bottom fishing. While 7% of the study region was found to be within MPA boundaries, only 2.5% of the region was subject to management measures that restrict mobile bottom fishing. Taking historical levels of fishing as a benchmark, management measures have been applied to <0.6% of the swept area of existing mobile bottom fishing activity. This may be explained by the higher average seabed ruggedness within MPA management measures, which was also where some key species of conservation interest were found. These findings suggest that protection has been focussed in areas that already act as natural refugia for sensitive benthic species and lie away from the majority of fishing activity. While the measures do not reduce fishing pressure markedly, they do protect relatively pristine habitats from future fishing impacts. MPA management measures had higher average seabed ruggedness, suggesting a bias in protection for species and habitats within such areas.